Pajanan Pestisida Organoklorin Terhadap Diabetes Melitus Tipe-2 Pada Usia Muda: Tinjauan Literatur - husna, Mufidatul; Hartono, Budi (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
DMT2 is the most common type of diabetes in the world. In developed countries, diaÂ¬betes affects people over 65 years old. However, in Asia, the younger generation is also affected and the age onset of diabetes has declined. Several factors that may lead to early diabetes is changes in consumption and activity patterns. However, that should be noted that pestisides expusure by food and environmental pollutants can even be the reason behind the increasing incidence of type-2 diabetes mellitus. This study aims to provide a systematic review of the impact of pesticide exposure on the incidence of type-2 diabetes, especially at a young age. We performed articles search using Science Direct, Spinger Link, ProQuest, Pubmed and Scopus databases published since 2010 until 2020. In total, 10 scientific articles included in this study. Pesticide exposure is determined by the nature of the sources. Most studies showed a strong association between organochlorine pesticides and also the incidence of diabetes. The average age of the entire study was 43 years this has proven that there is a decrease in the onset of age of people with DMT2 in Asia. The results show that organochlorine pesticides had an impact on the incidence of DMT2 at a younger age. Someone with high levels of organochlorines serum will had a high blood glucose levels. Race may also effect the incidence of diabetes, it need to be assessed experimentally.